Isle of Man : Financial Sector Assessment Program Update; Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents the Financial System Stability Assessment Report on the Isle of Man (IOM). Financial sector regulation and supervision are generally of a high standard, and supervisory efforts are concentrated in those areas most relevant to the activities of financial institutions on the IOM. The Financial Supervision Commission (FSC) faces a conundrum because the major banks are subsidiaries of large international financial groups, to which they provide financing. The FSC is reconsidering to balance prudential requirements for liquidity and exposure to related parties against business needs that entail high exposures to the parent.